Pemanfaatan Internet Sebagai Media Masyarakat Pada Layanan Perpustakaan di Masa Pandemi COVID-19 - Fahrun Nisak Alhusna S.IP (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The progress of information and communication technology (ICT) is currently growing rapidly. so that a new media called the Internet was born. The internet has made it easier for people to communicate without knowing the barriers of space and time. Its use is like providing space for people to interact more easily and quickly. This interaction exists both in individuals and groups. This article uses a descriptive qualitative research method with a literature study approach. Based on the results of the study, the use of the internet network can make it easier for libraries to provide services to users or virtual communities which were originally developed face-to-face and then turned into online services during the COVID-19 pandemic. In addition, it provides convenience for users who need information by providing electronic sources of information for users who need access via the internet. As a support unit in the field of education, libraries during the COVID-19 pandemic must continue to provide good service to their users so that the library remains busy and up to date.